Optimizing operation of municipal wastewater treatment plants in China: The remaining barriers and future implications. (August 2019) - Lu, Jia-Yuan; Wang, Xue-Meng; Liu, Hou-Qi; Yu, Han-Qing; Li, Wen-Wei
Abstract: China's national development strategy now prioritizes environmental protection over economic growth, which has driven a rapid development of China's wastewater sector. In particular, the treatment capacity of municipal wastewater treatment plants (WWTPs) has been substantially strengthened and stricter effluent quality control enforced. However, the operating performance of most WWTPs is still poor and does not meet the sustainable development demands. In this study, the current status of WWTPs operation in China was comprehensively analyzed, the key barriers to improving the plants operating efficiency were identified by taking into account the different plant scales, geographic distribution, discrepancy between cities and counties, and the influence of environmental policies and supplementary facilities. The underdeveloped sewer network was mainly responsible for the low operating ratios (i.e., utilization degree of the designed treatment capacity) of the plants (76% in counties and 85% in cities) especially for those in north China, although the situation is plant specific because a considerable fraction of plants (19%) are still running under overload condition. Other challenges include the high energy consumption of the plants (0.313 kWh/m 3 ), and severely lagged implementation of sludge disposal (up to 40% sludge was still improperly disposed), arising mainly from the poor management on the sewer and sludge. Lastly, several possible directions of improvement to overcome these barriers were discussed. This work may provide valuable implications for optimizing municipal wastewater management in China towards higher efficiency and sustainability. Graphical abstract: Unlabelled Image Highlights: Current status of municipal WWTPs operation in China was evaluated. Operation performances in different regions, centralized degrees and plant sizes were specified. Undeveloped sewers were responsible for low operating ratio of WWTPs. High energy consumption and laggard sludge disposal restrict the WWTPs upgrading. Optimizing WWTPs operation requires better technologies and improved management.